2008
DOI: 10.1002/ijc.23328
|View full text |Cite
|
Sign up to set email alerts
|

The combination of epigallocatechin gallate and curcumin suppresses ERα‐breast cancer cell growth in vitro and in vivo

Abstract: Both epigallocatechin gallate (EGCG) and curcumin have shown efficacy in various in vivo and in vitro models of cancer. This study was designed to determine the efficacy of these naturally derived polyphenolic compounds in vitro and in vivo, when given in combination. Studies in MDA-MB-231 cells demonstrated that EGCG 1 curcumin was synergistically cytotoxic and that this correlated with G 2 /M-phase cell cycle arrest. After 12 hr, EGCG (25 lM) 1 curcumin (3 lM) increased the proportion of cells in G 2 /M-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 58 publications
3
78
0
2
Order By: Relevance
“…For example, EGCG (50 mg kg À1 , s.c.) was minimally effective at reducing tumour growth in a MDA-MB-231 xenograft model, but acetylating EGCG and thus turning it into a pro-drug enhanced its efficacy (Landis-Piwowar et al, 2007). In a similar xenograft model, the efficacy of EGCG was increased by the addition of curcumin (Somers-Edgar et al, 2008). However, the overall tumour volume was only decreased by 49% as compared with control after EGCG þ curcumin treatment, indicating that EGCG þ tamoxifen is a more effective combination therapy as tumour volume was decreased by 71% as compared with control.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, EGCG (50 mg kg À1 , s.c.) was minimally effective at reducing tumour growth in a MDA-MB-231 xenograft model, but acetylating EGCG and thus turning it into a pro-drug enhanced its efficacy (Landis-Piwowar et al, 2007). In a similar xenograft model, the efficacy of EGCG was increased by the addition of curcumin (Somers-Edgar et al, 2008). However, the overall tumour volume was only decreased by 49% as compared with control after EGCG þ curcumin treatment, indicating that EGCG þ tamoxifen is a more effective combination therapy as tumour volume was decreased by 71% as compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that EGCG or green tea extract has a modest inhibitory effect on ER-negative tumour growth (Landis-Piwowar et al, 2007;Thangapazham et al, 2007;Somers-Edgar et al, 2008). For example, EGCG (50 mg kg À1 , s.c.) was minimally effective at reducing tumour growth in a MDA-MB-231 xenograft model, but acetylating EGCG and thus turning it into a pro-drug enhanced its efficacy (Landis-Piwowar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations